Curriculum learning of visual attribute clusters for multi-task classification. (August 2018) - Sarafianos, Nikolaos; Giannakopoulos, Theodoros; Nikou, Christophoros; Kakadiaris, Ioannis A.
Highlights: Novel learning scheme that combines the advantages of multi-task and curriculum learning. Efficient correlation-based grouping of tasks based on hierarchical clustering. Extensive evaluation, analysis of covariates and ablation studies. Abstract: Visual attributes, from simple objects (e.g., backpacks, hats) to soft-biometrics (e.g., gender, height, clothing) have proven to be a powerful representational approach for many applications such as image description and human identification. In this paper, we introduce a novel method to combine the advantages of both multi-task and curriculum learning in a visual attribute classification framework. Individual tasks are grouped after performing hierarchical clustering based on their correlation. The clusters of tasks are learned in a curriculum learning setup by transferring knowledge between clusters. The learning process within each cluster is performed in a multi-task classification setup. By leveraging the acquired knowledge, we speed-up the process and improve performance. We demonstrate the effectiveness of our method via ablation studies and a detailed analysis of the covariates, on a variety of publicly available datasets of humans standing with their full-body visible. Extensive experimentation has proven that the proposed approach boosts the performance by 4%–10%.